2020
DOI: 10.3389/fevo.2020.569425
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental DNA Survey on Distribution of an Endangered Salmonid Species, Parahucho perryi, in Hokkaido, Japan

Abstract: For protecting endangered species, precise understanding of their distribution is crucial. However, it is often very difficult to estimate at a large scale with conventional methods (e.g., casting nets or electrofishing for aquatic species) because of their low densities in the wild. Sakhalin taimen (Parahucho perryi) is one of the largest and most critically endangered freshwater salmonid fishes in the world. In this study, we applied an environmental DNA (eDNA) detection system for this species to 120 rivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
14
1
Order By: Relevance
“…The watershed-scale screening of their reproductive area based on eDNA is a practical approach for grasping spread of front-line of the invasive species because it has a potential to save high labour cost for the pondscale inspection by the direct observation methods. Although increasing number of eDNA studies have been conducted upon aquatic invasive and endemic species for their management (Adrian-Kalchhauser and Burkhardt-Holm 2016; Mizumoto et al 2020;Mauvisseau et al 2021), our study sheds light on an opportunity of their application to terrestrial species with limited period of time for reproduction in and around the watershed in a river basin.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The watershed-scale screening of their reproductive area based on eDNA is a practical approach for grasping spread of front-line of the invasive species because it has a potential to save high labour cost for the pondscale inspection by the direct observation methods. Although increasing number of eDNA studies have been conducted upon aquatic invasive and endemic species for their management (Adrian-Kalchhauser and Burkhardt-Holm 2016; Mizumoto et al 2020;Mauvisseau et al 2021), our study sheds light on an opportunity of their application to terrestrial species with limited period of time for reproduction in and around the watershed in a river basin.…”
Section: Discussionmentioning
confidence: 94%
“…Positive detection was defined as at least one detection in six PCR replicates per site (two filters/site and three qPCR replicates/filter), and lowest detection limit was set at 0.01 copy per 2 lL, following Mizumoto et al (2020). We had three temporal samples in Ino Riv.…”
Section: Environmental Dna Extraction and Amplificationmentioning
confidence: 99%
“…In addition, sterilized distilled water samples were applied in all qPCR assays as PCR negative control samples. Based on Mizumoto et al (2020), we accepted sites as positive detections with at least one detection in six PCR replicates per site and lowest detection limit was set at 0.01 copy per 2 µL× site. We had three temporal samples in Ino Riv.…”
Section: Dna Extraction and Detectionmentioning
confidence: 99%
“…Environmental DNA (eDNA) methods, which involve analyzing water samples for genetic material liberated by a target species without direct handling or observation of the organisms (Kelly et al, 2014; Lodge et al, 2012), have shown promise in alleviating some of these issues. Monitoring eDNA has been used to detect invasive species (Dejean et al, 2012; Sepulveda et al, 2020), monitor species of conservation concern (Deiner et al, 2021; Mizumoto et al, 2020), identify the presence of biological pollutants (Smith et al, 2015; Yamahara et al, 2015), and characterize the biodiversity of various marine and freshwater ecosystems (Ruppert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%